Sequestration and Cyanobacterial Diet Preferences in the Opisthobranch Molluscs Dolabrifera nicaraguana and Stylocheilus rickettsi - Clark, Kasey E.; Capper, Angela; Liu, Wei-Ting; Fenner, Amanda M.; Almanza, Alejandro; Della Togna, Gina; Herrera, Liuris; Johns, Timothy; Paul, Valerie J.; Dorrestein, Pieter C.; Capson, Todd L.; Balunas, Marcy J. (Frontiers in Marine Science, 2021)
A multidisciplinary approach was used to assess chemical ecological dietary interactions between marine organisms as a tool to isolate novel ecologically relevant compounds with biotechnological potential. First, laboratory-based feeding preference assays of the sea hare Dolabrifera nicaraguana (previously known as D. dolabrifera), an anaspidean mollusc, were conducted by simultaneously offering six food options collected from nearby tidal pools in the Coiba National Park in the Tropical Eastern Pacific of Panama. An evaluation of preferred dietary repertoire revealed D. nicaraguana significantly preferred cf. Lyngbya sp. over the cyanobacterium Symploca sp., green alga Chaetomorpha sp., and red alga Spyridia sp. A no-choice feeding assay using cf. Lyngbya sp. or green alga Cladophora sp. supported this finding. Secondly, we conducted bioactivity-guided fractionation using the preferred food source of D. nicaraguana, the ‘hair-like” cf. Lyngbya sp. from which we also isolated and elucidated two new depsipeptide compounds, veraguamide M (1) and veraguamide N (2). Veraguamides M (1) and N (2) showed in vitro activity toward the malaria-causing parasite Plasmodium falciparum with GI50 values of 4.2 and 4.3 μM, respectively, and therapeutic windows of 7.0–8.0 (based on moderate cytotoxicities to mammalian Vero cells with GI50 values of 29.3 and 34.1 μM, respectively). Veraguamide N (2) was also active against Leishmania donovani, the causative agent of visceral leishmaniasis, with a GI50 value of 6.9 μM. We then evaluated sequestration of these new compounds by D. nicaraguana used in the feeding assays and found trace amounts of the dietary sequestered compounds. Finally, we evaluated sequestration of these new compounds by the sea hare Stylocheilus rickettsi (previously known as S. striatus) that were grazing on the cf. Lyngbya sp. used in the feeding assays and found both to be sequestered. This study is the first example whereby compounds with significant activity against tropical parasites have been found in both the sea hare S. rickettsi and its cyanobacterial food source. These results suggest that chemical ecological studies involving sea hares and cyanobacteria continue to provide a diverse source of bioactive compounds with biotechnological potential.